All Days 2012
DOI: 10.2118/150337-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Optimization of an Emulsified Acid Blend for Stimulation of High-Temperature Carbonate Reservoirs

Abstract: Emulsified hydrochloric (HCl) acid has been used in both fracture and matrix acidizing of carbonate reservoirs to help penetrate deeper into the reservoir before spending. The emulsion stability and adequate corrosion inhibition are critical requirements of this blend, which are challenging to accomplish using emulsified acids of high HCl acid concentration (>26%) at high temperatures (>250°F) because many corrosion inhibitors used in the industry can severely affect emulsion stability by interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…It is reported that both the addition rate of the dispersed phase and mixing intensity govern the type of emulsion; a coarse emulsion will be the result of adding the dispersed phase to the continuous phase in one step without intensive mixing. However, a fine emulsion can be produced by adding the dispersed phase in atomized form coupled with intensive mixing [20,38].…”
Section: Emulsion Preparationmentioning
confidence: 99%
“…It is reported that both the addition rate of the dispersed phase and mixing intensity govern the type of emulsion; a coarse emulsion will be the result of adding the dispersed phase to the continuous phase in one step without intensive mixing. However, a fine emulsion can be produced by adding the dispersed phase in atomized form coupled with intensive mixing [20,38].…”
Section: Emulsion Preparationmentioning
confidence: 99%
“…Water in oil emulsions provide better retardation due to the low diffusivity created by the oil phase around acid droplets, which allows for minimum acid volume contact with t h e r o c k − t u b u l a r s u r f a c e . T h u s , m o s t r esearch 18,26,[29][30][31][32][33][34][35][36][37]39,40,[42][43][44][45][46][47][48][49][50][51]53 has adapted W/O emulsions due to their desirable retardation effect and corrosion inhibition in comparison to O/W emulsions, 27,28 as depicted in Figure 5.…”
Section: Emulsion Type On the Basis Of The Dispersionmentioning
confidence: 99%
“…Additives such as corrosion inhibitors and emulsifiers can be adsorbed and lost on to the rock surface, resulting in emulsion destabilization, increased chances of formation damage, and unwanted corrosion scale generation. 37,43 5.3. Emulsifier Concentration.…”
Section: Synthesis and Important Parameters For Ensuring Quality Emul...mentioning
confidence: 99%
“…Hence, the delayed nature of emulsified acid has attracted the attention of the oil and gas industry as it could decrease the reaction rate, reduce the contact between acid and well tabular and minimise corrosion issues that is related to well integrity, cost and above all issue associated with safety and environment. In carbonate matrix acidizing using emulsified acid, longer conductive flow paths or "wormholes" are induced, thus improving the permeability and productivity of the reservoir (Sabhapondit et al 2012;Al-Zahrani 2013;Fattah and Nasr-El-Din 2008). Experimental studies and real field application has indicated that emulsified acid can improve carbonate porosity and permeability while minimizing corrosion issues (Sayed et al 2013;Zakaria et al 2012;Navarrete et al 1998;Al-Anazi et al 1998).…”
Section: Introductionmentioning
confidence: 99%